Polyamine catabolism via spermine oxidase in the pathogenesis and treatment of hyperglycemia and diabetes mellitus-A short discussion - Ahmed Sean Alford (Open Journal of Cell and Protein Science - Peertechz Publications, 2023)
Diabetes mellitus can be described as chronic, endocrine dysfunction of pathophysiological regulation related to glucose and insulin. Hyperglycemia is the most common and intensely related complication of this dysfunction and has countless methods of pathogenicity. Hyperglycemia has the ability to exacerbate a degenerative positive feedback loop within critical tissues. Considering the fact that pancreatic hormonal regulation has played an increasingly considerable role in serum glucose homeostasis, here we begin a discussion into the implication of polyamine catabolism as a pathway with a mechanism that would contribute considerably to the necrosis and dysfunction of islet cells in the pancreas. The pathogenicity of this mechanism focuses on how the sustained increase in free radical production by hyperglycemic induction extenuates several complications in diabetes mellitus. The oxidation of spermine to spermidine produces hydrogen peroxide, as well as 3-aminopropanol (which spontaneously converts to acrolein) and spermidine (the precursor for the substrate of this reaction). This increase in reactive oxygen species exhibits the ability to inhibit autophagy and apoptosis as well as stimulate fat necrosis within the cells of the pancreas. Considering the islet cells of the pancreas play an extremely important role in glucose homeostasis, small changes in concentrations of these ROS are able to eliminate large regulatory factors while going undetected in the analysis of disease processes and therapeutics.